GAMBARAN PENGETAHUAN, SIKAP, DAN PRAKTIK PASIEN DENGAN PENYAKIT KRONIK DALAM MENCAPAI SPIRITUAL WELL BEING - Jamil, Nurul; Fajar Yousriatin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Spiritual needs are an essential component of holistic care that must be addressed in every patient. These needs are particularly important for individuals with chronic illnesses, terminal conditions, and those receiving palliative care. The ideal spiritual condition for patients is the achievement of spiritual well-being. However, not all patients are able to attain this state due to various influencing factors. This study aimed to describe patients' knowledge, attitudes, and practices related to achieving spiritual well-being. A descriptive case study design was employed involving patients with chronic diseases. A total of 32 participants were recruited, consisting of patients with chronic kidney disease, stroke, and infectious diseases. The findings revealed that the patients' levels of knowledge, attitudes, and practices ranged from fair to poor. These results indicate that regardless of their health condition, all patients continue to require spiritual support as an integral part of their personal experience. Therefore, patients need continuous education to develop adequate knowledge and positive attitudes that will enable them to achieve optimal spiritual well-being.